Strengthening gender capacities for organizational effectiveness - Mulema, Annet A. (International Livestock Research Institute, 2019)
This film highlights the results of a three-year initiative (2015-17) by ILRI and the International Center for Agricultural Research in the Dry Areas (ICARDA) to strengthen the gender capacities of local partners in Ethiopia through training in the use of gender mainstreaming strategies, experimentation and coaching.